2006
DOI: 10.1111/j.1365-2958.2006.05373.x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the gliP gene of Aspergillus fumigatus results in loss of gliotoxin production but has no effect on virulence of the fungus in a low‐dose mouse infection model

Abstract: SummaryGliotoxin is a secondary metabolite produced by several fungi including the opportunistic human pathogen Aspergillus fumigatus. As gliotoxin exerts immunosuppressive effects in vitro and in vivo, a role as a virulence determinant in invasive aspergillosis has been discussed for a long time but evidence has not been provided until now. Here, by the use of different selection marker genes A. fumigatus knock-out strains were generated that are deficient for the nonribosomal peptide synthetase GliP, the put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
146
4
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 150 publications
(160 citation statements)
references
References 48 publications
6
146
4
2
Order By: Relevance
“…While this approach is acceptable, the number of fungal metabolites which can be present in organic extracts, combined with the possibility of peptide generation due to unwanted proteolysis, demands a more rigorous confirmation of gliotoxin presence. LC-MS analysis of gliotoxin fulfils this criterion; however, this is a relatively specialised technique and is not available to all researchers [12,15,16]. Moreover, alternative bioassay formats have also been proposed for detection of gliotoxin and related epipolythiodioxopiperazines, of fungal origin, at levels of 18-20 ng well −1 [19,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this approach is acceptable, the number of fungal metabolites which can be present in organic extracts, combined with the possibility of peptide generation due to unwanted proteolysis, demands a more rigorous confirmation of gliotoxin presence. LC-MS analysis of gliotoxin fulfils this criterion; however, this is a relatively specialised technique and is not available to all researchers [12,15,16]. Moreover, alternative bioassay formats have also been proposed for detection of gliotoxin and related epipolythiodioxopiperazines, of fungal origin, at levels of 18-20 ng well −1 [19,25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on gliotoxin biosynthesis, which have demonstrated the role of the non-ribosomal peptide synthetase, GliP, in mediating the initial step of gliotoxin formation, have also deployed LC-MS to detect the presence and absence of gliotoxin in wild-type and mutant (ΔgliP) cultures from A. fumigatus [16]. Moreover, using a chemical reduction and alkylation strategy, thiol and disulphide absence has been confirmed in a gliotoxin-like metabolite isolated from an A. fumigatus mutant deficient in gliotoxin biosynthesis [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear whether these secondary metabolites contribute to virulence, because the role and production of these compounds during infection has hardly been investigated yet. An exception is the immune modulator gliotoxin, which was re-isolated from infected mouse lungs Kupfahl et al, 2006), but, also for this metabolite, the impact on virulence is still under discussion. A hint for the general impact of secondary metabolites on virulence derives from investigations on A. fumigatus mutants, which carry a deleted leaA gene.…”
Section: Discussionmentioning
confidence: 99%
“…This latter assumption has been tested recently by two research groups who disrupted the peptide synthetase gene in the biosynthetic pathway and studied the effect of these non-gliotoxin-producing mutants in vitro and in vivo in animal models. The mutants showed reduced cytotoxic activity on cells such as mast cells or macrophages but did not affect the survival of mice with invasive aspergillosis (23,47). Thus, gliotoxin does not appear to be required for the pathogenicity of the fungus in immunocompromised mice.…”
Section: Developmental Regulation Of Pathogenesismentioning
confidence: 96%